Lateral Lymph Node Metastases in T1a Papillary Thyroid Carcinoma: Stratification by Tumor Location and Size - Zhang, Xiaojun; Chen, Wenkuan; Fang, Qigen; Fan, Jie; Feng, Lu; Guo, Lanwei; Liu, Shanting; Ge, Hong; Du, Wei (Frontiers in Endocrinology, 2021)
Objective: To analyze the incidence and risk factors for lateral lymph node metastases (LNM) in T1a papillary thyroid carcinoma (PTC) with a focus on tumor location and size. Materials and Methods: The incidence of lateral LNM in 345 cases of T1a PTC was retrospectively analyzed. Univariate and multivariate analyses were performed to assess the relationships between lateral LNM and clinicopathological characteristics. Results: The incidence of skip metastasis to lateral LNM in T1a PTC located in the upper lobe was 12.1% (8/66). Logistic regression analysis indicated tumor size >5 mm (OR=5.04, 95% CI = 1.79 to 14.18, P=0.002), upper lobe location (OR=7.68, 95% CI = 3.05-19.34, P<0.001) and the number of central neck LNM (<2: OR=24.79, 95% CI = 8.23-74.60, P<0.001; 2: OR=4.99, 95% CI =1.95-12.73, P<0.001) were independently associated with lateral LNM. Comparing the lateral and central LNM stratification based on tumor location revealed that both the incidences of lateral (33.3%) and central (30.3%) LNM of T1a PTC located in the upper lobe were higher than that of T1a PTC located in the middle and lower lobes. Of T1a PTC located in the upper lobe, the incidence of lateral LNM was 33.3% (22/66), which was higher than that (30.3% (20/66)) of central LNM. This finding is reversed in all T1a PTC cases and T1a PTC cases with tumor located in the middle and lower lobes. Conclusion: A particularly high likelihood of lateral LNM was observed in T1a PTC patients with tumor located in the upper lobe of the thyroid gland, especially the tumor >5 mm in size, which could be considered a risk factor for lateral LNM in the clinical management of T1a PTC. Keywords: Papillary thyroid carcinoma; Lymph node metastases; upper lobe